A influência do feedback verbal na cooperação em crianças - Dutra, Natalia Bezerra (2012)
Human cooperation is a hallmark of this species due to its wide extension to genetically unrelated individuals and complex division of labor. It is considered an evolutionary puzzle, because the theory of evolution by natural selection predicts that self-interested individuals tend to be selected. Different theories have been proposed to explain the evolution of cooperation, which the most important are kin selection and reciprocal altruism. Considering the evolutionary continuity between species, humans and other primates have several common traits that help to promote cooperation between individuals of these species. Two features, however, seem to be particularly humans: inequality aversion and preferences in relation to others. Although human cooperation is not necessarily related to morality, cooperative traits are the basis for moral tendencies. The development of human morality is a combination of early prosocial tendencies, cooperative skills displayed at different ages, social learning and cultural transmission of norms. The social stimulus seems to be particularly important in promoting cooperative behavior in children and adults. In order to study the influence of social stimuli, as verbal feedback, on children cooperation, a study was conducted with children in a public goods game. 407 children from public schools in Natal / RN, divided into 21 groups, between six and nine years, participated in eight rounds of this game. After each round, seven groups received praise for larger donations, seven groups have been criticized by smaller donations, and the other seven received no comment. Children cooperated more when criticized, without significant differences between sexes, although young children have cooperated more negative than older children. The results are likely related to the anticipation and avoidance of punishment associated with the feedback (although this did not occur), and greater sensitivity to the authority in younger children. Nevertheless, the cooperation decreased in all groups until the last day of play. The results suggest an early sensitivity to moral punishment, whose role in the maintenance of social relations must have been important in the evolution of cooperation in humans